2018
DOI: 10.1021/acs.nanolett.8b01480
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Photovoltage Plateau in Large Bandgap Perovskite Photovoltaics

Abstract: Development of large bandgap (1.80-1.85 eV E) perovskite is crucial for perovskite-perovskite tandem solar cells. However, the performance of 1.80-1.85 eV E perovskite solar cells (PVKSCs) are significantly lagging their counterparts in the 1.60-1.75 eV E range. This is because the photovoltage ( V) does not proportionally increase with E due to lower optoelectronic quality of conventional (MA,FA,Cs)Pb(I,Br) and results in a photovoltage plateau ( V limited to 80% of the theoretical limit for ∼1.8 eV E). Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 55 publications
(134 reference statements)
3
89
0
Order By: Relevance
“…Further improvements in V OC have been achieved by the same group, through the incorporation of phenethylammonium iodide (PEA) into MAPb(I 0.6 Br 0.4 ) 3 . It was found that lower photovoltage for conventional (MA,FA,Cs)Pb(I,Br) 3 was attributed to lower optoelectronic quality and resultant photovoltage plateau ( V OC limited to 80% of the theoretical limit for ≈1.8 eV E g ).…”
Section: Current Research Trends In Tandem Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further improvements in V OC have been achieved by the same group, through the incorporation of phenethylammonium iodide (PEA) into MAPb(I 0.6 Br 0.4 ) 3 . It was found that lower photovoltage for conventional (MA,FA,Cs)Pb(I,Br) 3 was attributed to lower optoelectronic quality and resultant photovoltage plateau ( V OC limited to 80% of the theoretical limit for ≈1.8 eV E g ).…”
Section: Current Research Trends In Tandem Devicesmentioning
confidence: 99%
“…Based on the compositional versatility of metal halide perovskites (ABX 3 ), the most commonly used approaches for bandgap tuning include A-site compositional engineering (FA/Cs), [22,35,40,44] B-site modification (Pb/Sn binary alloys) [87][88][89] and incorporation of Br at the C-site. [40,45,90] The inclusion of FA/Cs into highbandgap mixed-halide perovskites can significantly increase the stability and energetic order, while reducing the tendency toward phase-segregation. The presence of MA cation can reduce a substantial lattice mismatch between Cs and FA and, thereby, slow down the perovskite crystallization process to achieve defect-free films.…”
Section: Materials Designmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have negligible hysteresis depending on the scan direction (Figures S10c and S11c, Supporting Information) and rate (Figures S10d and S11d, Supporting Information), and their PCEs at the MPP (13.19 ± 0.09% and 12.75 ± 0.09% PCE for 1.87 and 1.89 eV, respectively) are comparable to those obtained by J – V scanning (Figures S10e and S11e, Supporting Information). Figure g and Table S2 (Supporting Information) summarize the recently reported performances of opaque wide‐bandgap perovskite PVs having their bandgap between 1.80 and 1.90 eV, and it is worth to note that, to the best of our knowledge, the wide‐bandgap perovskite PVs in this work show superior efficiencies in this bandgap range . Some of them represented higher V oc than our PV devices, but they had much lower J sc and FF, decreasing overall PCE (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Figure g and Table S2 (Supporting Information) summarize the recently reported performances of opaque wide‐bandgap perovskite PVs having their bandgap between 1.80 and 1.90 eV, and it is worth to note that, to the best of our knowledge, the wide‐bandgap perovskite PVs in this work show superior efficiencies in this bandgap range . Some of them represented higher V oc than our PV devices, but they had much lower J sc and FF, decreasing overall PCE (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%